Analisis Perbedaan Tingkat Persepsi Etika Mahasiswa Akuntansi Terhadap Earnings Management Berdasarkan Tingkat Pendidikan - Annisa Hakim Z; Arens Fideous Samben (JRAK: Journal of Accounting Research and Computerized Accounting, 2019)
This study aims to see the differences in accounting students' ethical perceptions of earnings management based on education level. The data used in this study are undergraduate and postgraduate students in the Economics and Business Faculty of Gadjah Mada University with a total sample of 109 consisting of 56 undergraduate students and 53 postgraduate students. The independence t-test was used to see the difference. The results showed that there were significant differences regarding the ethical perceptions of accounting students towards earnings management based on education level.